Modular growth vessels for the cultivation of the cyanobacterium Synechococcus sp. PCC 7002. Issue 1 (2nd January 2017) - Jackson, Simon A.; Eaton-Rye, Julian J.
ABSTRACT: Synechococcus sp. PCC 7002 is a euryhaline cyanobacterium that serves as a model organism for studies of photosynthesis and cellular metabolism. At high light intensity Synechococcus sp. PCC 7002 exhibits a fast growth rate and rapid biomass accumulation, making it an ideal candidate for the production of biofuels and commercially valuable secondary metabolites. To fully realise the production potential for this cyanobacterium a system is required to maintain axenic cultures under optimal growth conditions. We have designed and constructed two sizes of modular culture vessel systems, designed specifically to meet the abnormally high light penetration requirements of Synechococcus sp. PCC 7002. The smaller volume culture vessels are best suited to phenotype analysis, allowing multiple candidate strains to be screened simultaneously, whereas the larger vessels are designed to facilitate higher biomass production.